Muatan Kearifan Lokal pada Buku Bacaan Siswa Terbitan Kemdikbud - Aisyah Nur Fadhilah; Laili Etika Rahmawati (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2020)
This study aims to identify the content of local wisdom in the student reading books published by the Ministry of Education and Culture. This type of research is a qualitative descriptive study. The object of research is the content of local wisdom in the student reading books published by the Ministry of Education and Culture entitled “Kenara Anak Suku Gayo” and “Kain Kulit Kayu Dei”. The data from this study are student reading books published by the Ministry of Education and Culture which contain local wisdom. The data source in this research is an archive or document in the form of a student reading book published by the Ministry of Education and Culture which contains local wisdom. The data collection technique uses the technique of listening and note taking, the researcher first reads the reading book “Kenara Anak Suku Gayo” and “Kain Kulit Kayu Dei” published by the Ministry of Education and Culture to carefully determine the local wisdom content, then record thoroughly and analyze the reading into the wisdom content. local. Data analysis techniques using flow analysis. The results showed that the reading book “Kenara Anak Suku Gayo” contained five contents of local wisdom including: (1) culture, (2) norms, (3) ethics, (4) beliefs, and (5) customs. While the reading book “Kain Kulit Kayu Dei” there are only three contents of local wisdom including: (1) culture, (2) beliefs, and (3) customs.